Redescription of Ypsolopha nervosella (Zerny, 1940) (Lepidoptera, Ypsolophidae) with first description of the female genitalia - Baraniak, Edward; Walczak, Urszula (Zootaxa, 2014)
In three successive papers, Zerny (1939, 1940a, b) catalogued the specimens collected during his expedition to Iran. His description of the external appearance of Ypsolopha nervosella was very short (Zerny 1940b). He mentioned that Y. nervosella was similar to Y. instabilella (Mann, 1866) collected in the same location. Such a terse description of the species does not allow for its correct identification and therefore the status of the species has remained unclear. Following the examination of its type specimen, we provide a more extensive description, including that of its genitalia.